2007
DOI: 10.1152/ajpendo.00504.2006
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and insulin improve cardiac efficiency and postischemic functional recovery in perfused hearts from type 2 diabetic (db/db) mice

Abstract: Hafstad AD, Khalid AM, How OJ, Larsen TS, Aasum E. Glucose and insulin improve cardiac efficiency and postischemic functional recovery in perfused hearts from type 2 diabetic (db/db) mice. Am J Physiol Endocrinol Metab 292: E1288 -E1294, 2007. First published January 9, 2007; doi:10.1152/ajpendo.00504.2006.-Hearts from type 2 diabetic (db/db) mice demonstrate altered substrate utilization with high rates of fatty acid oxidation, decreased functional recovery following ischemia, and reduced cardiac efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 39 publications
7
61
0
1
Order By: Relevance
“…Taken together, these observations may suggest that long-term exposure to elevated circulating lipid levels under diabetic conditions leads to an adaptation to the increased FA load, which could improve resistance to the detrimental effect of an acute FA load. In addition, data from our laboratory have previously demonstrated that an acute inhibition of FA oxidation and increased glucose oxidation [induced by glucose and insulin (22) and DCA (unpublished data)] decreased MV O 2 and increased cardiac efficiency in db/db hearts. This shows that in contrast to that in nondiabetic hearts, there is a potential for improving cardiac efficiency by acute changes in substrate utilization in diabetic hearts.…”
Section: Discussionmentioning
confidence: 89%
“…Taken together, these observations may suggest that long-term exposure to elevated circulating lipid levels under diabetic conditions leads to an adaptation to the increased FA load, which could improve resistance to the detrimental effect of an acute FA load. In addition, data from our laboratory have previously demonstrated that an acute inhibition of FA oxidation and increased glucose oxidation [induced by glucose and insulin (22) and DCA (unpublished data)] decreased MV O 2 and increased cardiac efficiency in db/db hearts. This shows that in contrast to that in nondiabetic hearts, there is a potential for improving cardiac efficiency by acute changes in substrate utilization in diabetic hearts.…”
Section: Discussionmentioning
confidence: 89%
“…Using echocardiography, reduced fractional shortening and a reduction in the velocity of circumferential shortening have been demonstrated (Semeniuk et al, 2002;Carley et al, 2004;Pereira et al, 2006). Cardiac output, LV-developed pressure and cardiac power are all reduced in isolated, working db/db hearts, whereas LV end diastolic pressure is increased (Belke et al, 2000;Aasum et al, 2003;Carley et al, 2004;Hafstad et al, 2006;Hafstad et al, 2007). Similar contractile deficits are observed in Langendorff-perfused db/db hearts, in which ±dP/dt, peak systolic pressure, rate pressure product and developed pressure are all reduced Disease Models & Mechanisms DMM PERSPECTIVE .…”
Section: The Db/db Mousementioning
confidence: 99%
“…15,17 For example, in ex vivo mice hearts, glucose-insulin infusions improved glucose oxidation and contractile efficiency, while incretinbased therapies (Liraglutide and Exendin-4) reversed steatosis, oxidative stress and SERCA downregulation. [81][82][83][84] Limited data exist in humans, and some of them are at odds with findings in animals. In a retrospective analysis, biguanide (metformin) use was associated with reduced natiuretic peptide levels and lower cardiovascular morbidity and mortality.…”
Section: Diabetic and Hf Medicationsmentioning
confidence: 99%